Glomus mosseae Inoculation Improves the Root System Architecture, Photosynthetic Efficiency and Flavonoids Accumulation of Liquorice under Nutrient Stress - Chen, Meilan; Yang, Guang; Sheng, Ye; Li, Pengying; Qiu, Hongyan; Zhou, Xiuteng; Huang, Luqi; Chao, Zhi (Frontiers in Plant Science, 2017)
The poor quality and low productivity of cultivated liquorice (Glycyrrhiza uralensis) continues to put pressure on wild plant populations. As arbuscular mycorrhizal fungi are known to support plant growth and in some cases even to enhance the accumulation of valuable molecules in the plant, the effect of Glomus mosseae on the growth and active ingredient contents was evaluated in liquorice plants grown under nutrient deficiency. We created a nutrient-deficient environment by mixing paddy soil, washed river sand, and pumice at a ratio of 1:5:1. Our results showed that the inoculation of pot-grown liquorice plants with G. mosseae significantly increased the shoot and root biomass (by 25 and 17 folds, respectively) and the contents of glycyrrhizic acid, liquiritin, isoliquiritin, and isoliquiritigenin in the main root (by 1.6, 4.8, 6.5, and 4.4 folds, respectively). Both isoliquiritin and isoliquiritigenin were detectable in the lateral roots of the plants inoculated with G. mosseae, but not in plants without G. mosseae inoculation. G. mosseae inoculation improved the features of the root system and increased photosynthetic efficiency of liquorice. The uptake of P and K by liquorice increased when G. mosseae was inoculated, leading to the depletion of these macronutrients in the soil; G. mosseae also improved the availability of Mg, Cu, Zn, and Mn. Based on these results, we concluded that the inoculation of liquorice plants with G. mosseae is beneficial, particularly for those grown in nutrient-deficient soil, and such positive effect is related to the improvement of the root system and an increased photosynthetic efficiency.